Organizational Education & its Role in The Development of Human Efficiency - BENDJIMA, MERIEM (Finance and Business Economies Review, 2018)
Education is the process of providing individuals with a wealth of knowledge and knowledge in a particular framework. It is concerned with the development of knowledge as a means of qualifying the individual to enter the working life by increasing public information and understanding level to the outside world. The aim of education is to develop intellectual property and to acquire public and private knowledge, and obtaining certain professional qualifications that qualify them to join specific jobs